2008
DOI: 10.1002/hed.20936
|View full text |Cite
|
Sign up to set email alerts
|

Malignant fibrous histiocytoma of the sinonasal tract

Abstract: In this series, post-irradiated MFH was more common than primary MFH. The prognosis of post-irradiated MFH is poor, whereas primary MFH is fair.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 38 publications
2
33
0
3
Order By: Relevance
“…32 Lagrange et al reported that most RIS was high grade, as observed in our study, in which 66% were grade 3. 33 Regarding RIS site, the proportion of sarcomas that arose from the maxillary sinus in the current study cohort (18.9%) was consistent with the data reported by Wang et al 17 RIS traditionally has been viewed as an aggressive tumor with a generally poor prognosis. The 3-year OS rate for patients with RIS in our series (32.4%) was within the lower end of the wide range reported previously (8%-60% at 5 years).…”
Section: Radiation-induced Sarcoma In Npc/xi Et Alsupporting
confidence: 90%
“…32 Lagrange et al reported that most RIS was high grade, as observed in our study, in which 66% were grade 3. 33 Regarding RIS site, the proportion of sarcomas that arose from the maxillary sinus in the current study cohort (18.9%) was consistent with the data reported by Wang et al 17 RIS traditionally has been viewed as an aggressive tumor with a generally poor prognosis. The 3-year OS rate for patients with RIS in our series (32.4%) was within the lower end of the wide range reported previously (8%-60% at 5 years).…”
Section: Radiation-induced Sarcoma In Npc/xi Et Alsupporting
confidence: 90%
“…The study periods spanned the 1990s and/or 2000s, and dated back to the 1980s for 9 studies (Hsieh et al, 2003;Campbell et al, 2004;Hsu et al, 2004;Dickinson et al, 2006;Wu et al, 2006;Kim et al, 2007;2008c;Huang et al, 2010;Han et al, 2011) and the 1970s for 1 study (Wang et al, 2009) (Table 1). The number of patients [minimum, 12 (Jun et al, 2010); maximum, 324 (Dickinson et al, 2006) was fewer than 50 in 17 of the 32 studies.…”
Section: Study and Patient Characteristicsmentioning
confidence: 99%
“…The number of patients [minimum, 12 (Jun et al, 2010); maximum, 324 (Dickinson et al, 2006) was fewer than 50 in 17 of the 32 studies. Only 13 studies specified whether STS was primary or recurrent [8 primary (Dickinson et al, 2006;Hui et al, 2006;Wu et al, 2006;An et al, 2007;Kim et al, 2008a;Ng and Tan, 2009;Wang et al, 2009;Liu et al, 2010); 5 primary or recurrent (Hsieh et al, 2003;Kiatisevi et al, 2006;Moncrieff et al, 2008;Miki et al, 2010;Cho et al, 2011)]. Patients had local disease in 15 studies (Choong et al, 2003;Campbell et al, 2004;Hsu et al, 2004;Dickinson et al, 2006;Hui et al, 2006;An et al, 2007;Kim et al, 2007;2008c;Pervaiz et al, 2008;Rudiger et al, 2009;Wang et al, 2009;Liu et al, 2010;Cho et al, 2011;Han et al, 2011), and local or metastatic disease in 7 studies (Wu et al, 2006;Chan et al, 2008;Moncrieff et al, 2008;Koh et al, 2009;Jun et al, 2010;Park et al, 2010;Lee et al, 2011).…”
Section: Study and Patient Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations